واقع وتحديات الرقابة الشرعية في المصارف الإسلامية - بن عمارة, نوال (Sciences humaines, 2014)
يأتي هذا البحث في إطار الاهتمام   بالرقابة الشرعية، لما لها من دور فعال في النهوض بالمصارف الإسلامية ، متناولاً دورها ، وطبيعة عملها ، وكذا مقوماتها وأساليبها ومهام هيئة الرقابة الشرعية ومدى إلزامية قراراتها        مع استعراض أهم المعوقات ونقاط الضعف التي تعاني منها وصولا إلى اقتراح الحلول والمتطلبات اللازمة لزيادة كفاءتها وفاعليتها لتحقيق أهدافها. الكلمات المفتاحية : الرقابة الشرعية ، هيئة الرقابة الشرعية ، المصارف الإسلامية.   This research in the context of attention on legal supervision because of its effective role in promoting Islamic banks, it addressed the role and nature of its work, as well as its components, methods and tasks the legal supervisory board and extent obligatory resolutions with a review of main obstacles and weaknesses afflicting up to propose solutions and requirements to increase the efficiency and effectiveness to achieve its objectives. Keywords: legal supervision, legal supervisory board, Islamic banks.